Konsep Pergaulan Baik dalam Perspektif Al-Quran : (Telaah dalam Perspektif Maudhui) - Nuril laila, Nuril Laila; Wiwin Ainis Rohtih; Ahmad Zainuddin; Nyoko Adi Kuswoyo (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This analytical study aims to understand the concept of good relationships in the Al-Qur'an. By using qualitative research methods and thematic interpretation methods (maudhu'i), this research found that the concept of good social relations in the Al-Qur'an found six verses related to good social relations. Where each verse will be interpreted by the scholars to find the results of an intelligent social attitude. Apart from that, a definition of social relations is also presented which includes the definition of good social relations according to the Al-Qur'an, as well as social ethics which emphasize mutual respect and appreciation, the last of which will be presented regarding the discussion of the impact of promiscuity. Thus, this study not only deepens social relationships but also provides the perspective of the Al-Qur'an that every Muslim must live by.